2015
DOI: 10.4028/www.scientific.net/jnanor.36.1
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Properties of (Ba<sub>1-(x+y)</sub>Sr<sub>x</sub>Eu<sub>y</sub>)<sub>2</sub>Si<sub>6</sub>O<sub>12</sub>N<sub>2</sub> Phosphors for White LED Applications

Abstract: (Ba1-(x+y)SrxEuy)2Si6O12N2 oxynitride phosphors were successfully synthesized by the solid-state reaction method at 1200°C under a H2(5%) + N2(95%) atmosphere. The Sr2+ content (x) was varied in the range 0-0.6 and the Eu2+ content varied in the range 0.05-0.25, with the Si/(Ba+Sr+Eu) ratio fixed at 3. Results showed that the emission characteristics of (Ba1-(x+y)SrxEuy)2Si6O12N2 phosphors under UV or blue-light excitation was strongly dependent on the chemical composition. The phosphor (Ba0.95Eu0.05) Si6O12N2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Both samples are much similar to large particle size and irregular morphologies. This result is also in line with the synthetic experiments of Moriga et al, who reported that a higher Si/Ba ratio was beneficial for the synthesis of Ba 3 Si 6 O 12 N 2 and (Ba 1–( x + y ) ­Sr x Eu y ) 2 ­Si 6 O 12 N 2 phases. , …”
Section: Resultssupporting
confidence: 91%
“…Both samples are much similar to large particle size and irregular morphologies. This result is also in line with the synthetic experiments of Moriga et al, who reported that a higher Si/Ba ratio was beneficial for the synthesis of Ba 3 Si 6 O 12 N 2 and (Ba 1–( x + y ) ­Sr x Eu y ) 2 ­Si 6 O 12 N 2 phases. , …”
Section: Resultssupporting
confidence: 91%
“…The main difficulty when tackling this question is that a change of a compound's structure is usually linked to a change in its composition and vice versa. The influence of the composition can be evaluated by studying the effect of a partial substitution of one or more of the constituting elements in a system, which tolerates this substitution without undergoing structural change [17][18][19][20][21][22][23]. Much rarer is the case of a host structure which exhibits polymorphism, like e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that partially replacing Ba 2+ ( r Ba2+ = 149 pm) ions in the host lattice with smaller Sr 2+ ( r Sr2+ = 132 pm) ions can lead to unit cell volume contraction. As a consequence, the local coordination environment around Eu 2+ ions is modified, and the corresponding luminescence properties are improved . On the basis of this consideration, we prepared a series of (Ba, Sr) 3 (Al, Si) 6 (O, N) 15 :Eu 2+ samples and studied the structure and luminescence properties in detail.…”
Section: Resultsmentioning
confidence: 99%